Alterações metabólicas em idosos que realizaram cirurgia bariátrica: um estudo retrospectivo - Zemolin, Cleide Monteiro (2022)
In parallel with the increase in aging, the world also faces a growing increase in obesity in all age groups, including among the elderly. This is a worrisome fact, since obesity alone is an independent risk factor for other associated comorbidities and metabolic syndrome (MS). It is a chronic condition of multifactorial etiology and its treatment involves several approaches (nutritional, use of medications and practice of physical exercises). However, several patients do not respond to these therapeutic approaches, requiring more invasive interventions. In this sense, bariatric surgeries have been assuming an important role as the last therapeutic strategy, demonstrating good control of comorbidities in conjunction with weight loss. The aim of this study was to identify and analyze metabolic alterations in elderly people who underwent bariatric surgery within one year. This is a retrospective study with a quantitative approach. The sample was characterized by patients aged 60 years or older, submitted to bariatric surgery in a private clinic in southern Brazil, from 2015 to 2020, according to the established inclusion and exclusion criteria. The selection of participants and data collection took place through consultation in the clinic database. For data extraction, a form was used with the following variables: sociodemographic, anthropometric data, personal health data and clinical data. Anthropometric data and laboratory results were collected in three stages: pre-surgical, six months and one year after surgery. Data were collected from June to September 2021. The software used for statistical analysis was SPSS version 21.0. To evaluate the behavior of the variables over time and between group, a model of generalized estimation equations was used, complemented by the Least Significant Difference test. For better interpretation of the results in relation to weight loss, we divided the patients into two subgroups: by gender (male and female) and by age group (60 to 65 years and 66 to 71 years). The results showed remission of comorbidities in dyslipidemia, gastroesophageal reflux, sleep apnea and hepatic satosose, and partial control in diabetes (88%), hypertension (92%) and depression (39%). Bmi went from obesity (mean of 42.72kg/m²) to overweight (mean of 27.70kg/m²) in the first year evaluated. There was a reduction in the use of alcohol and tobacco and an improvement in the practice of physical activities, as well as in the number of medications in use; we showed loss of lean mass in the first six months, with stabilization after the first year, with progressive loss of fat mass. Regarding weight loss between age groups, there was no significant difference between them. Bariatric surgery of gastric bypass in Roux-of-Roux via laparoscopic was shown to be effective in the metabolic profile of the elderly population in a short period.